Chemical Composition and Nutritional Analysis of Seeds Cactus (Opuntia ficus-indica.L) - Benattia, Farah K.; Arrar, Zoheir; Dergal, Fayçal (Current Nutrition & Food Science, 2019)
Background: The Prickly pear
Keywords: seeds